Travel journalism :informing tourists in the digital age - Pirolli, Bryan (Routledge, 2019)
"In the last decade, with the success of review sites and online commentaries and the increased accessibility more generally of travel information online, the job of a traditional travel journalist is being challenged. Travel Journalism seeks to examine more closely the impact of digital media and technology on this specialist area of journalism and how professionals working in travel media today are adapting to it. Bryan Pirolli draws on a wealth of professional experience to present both practical guidance and theoretical analysis of travel journalism. Through interviews with content providers - including journalists and bloggers - the book opens up new ways of thinking about this profession. It looks at relationship between travel journalists, social media and influencers, asking how travel journalists might rethink their work for more constructive purposes. The book asks how journalists should respond to innovations like the ever-growing sharing economy and multi-media storytelling. It also explores how journalistic ethics can be preserved whilst concerns around "fake news,' "sponsored content," and "paid influencers" remain widespread. For students and professionals looking to better understand the role of the travel journalist in the digital age, this book will be an invaluable resource. It comprehensively assesses the challenges and opportunities for success that actors in travel media are now presented with and encourages readers to pro-actively embrace them"--